Periodization of training for team sports athletes - Gamble, P. (Strength and Conditioning Journal, 2006)
Training variation and periodization is widely acknowledged as crucial to optimizing training responses. Applying periodized planning to team sports poses unique challenges due to the variety of training goals, volume of concurrent training and practices, and extended season of competition. Practical suggestions are offered in this article to address these considerations and apply periodization in training design for different phases of physical preparation for team sports athletes.